Dependence of demodulation performance on symbol rate for underwater acoustic communication with nonuniform Doppler shift. (11th June 2019) - Deguchi, Mitsuyasu; Kida, Yukihiro; Watanabe, Yoshitaka; Shimura, Takuya
Abstract: In underwater acoustic communication between surface and underwater vehicles, the nonuniform Doppler shift can degrade demodulation performance severely depending on the symbol rate. In this paper, the dependence of demodulation performance on the symbol rate is investigated using simulations with and without a multipath signal. The results show that symbol rate plays an important role in determining demodulation performance under an environment with a nonuniform Doppler shift. Furthermore, the simulation results without a multipath signal indicate that the effects of a nonuniform Doppler shift of a direct signal can be suppressed at a relatively low symbol rate. On the other hand, the simulation results with a multipath signal show that a high symbol rate is required to suppress the effect of the multipath signal under an environment with a nonuniform Doppler shift.